Study of the chemical content of the acetone extract of the leaves and fruits of the Arbutus plant using gas chromatography-mass spectrometry (Latakia University Journal -Biological Sciences Series, 2023)
The research was conducted during / 2022-2023/  in Tishreen university- the higher institute of ecological research where leaves and fruits of arbutus plant were collected from Banias city, and the acitonic extract of both leaves and fruits of arbutus was obtained.The chemical content of dry and wet leaves and fruits acitonic extract was analyzed by  a gas chromatography device – mass spectrum GC/MS in the higher institute of marine research for specifying the chemical content and knowing the most effective chemicals.The study has shown the existence of (8) compounds in the wet acitonic extract of leaves whereas the dry acitonic extract of leaves had (48) compounds, while the acitonic extract of fruits had only (25) compounds, the compound2-Furancarboxaldehyde, 5-(hydroxym Methyl) recorded the highest ratio (12.08%) within the compounds of wet acitonic extract of leaves, whereas the compound n-Hexadecanoic acid  had the highest ratio (20.9%) among the dry acitonic extract of leaves, while the compound  2-Furancarboxaldehyde, 5-(hydroxym  ethyl) of the dry extract of leaves recorded the highest ratio (12.67%) among the compounds of acitonic extract of fruits.